Konsepsi dan Implementasi Penilaian Literasi Membaca Berbasis HOTS dalam Bahasa Inggris - Elin Driana; Ernawati Ernawati (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
Reading literacy plays an important role in determining one's success in pursuing education, entering the workforce, and navigating daily life. In facing the challenges of the 21st century with increasing globalization and the abundance of information in various forms, the education system needs to prepare students with high-level thinking skills in reading literacy so that they learn to manage and interpret various information critically. This research aims to explore English teachers' conceptions of assessing high-order thinking skills (HOTS) in reading literacy and its implementation. Data were collected through semi-structured interviews with 10 English teachers in Jakarta. The results of the study indicate that teachers define HOTS assessment in reading literacy as higher-order thinking abilities compared to mere recall, referring to the revised Bloom's taxonomy. Most teachers in this study also understand HOTS assessment as evaluating students' abilities to transfer knowledge, think critically, think creatively, solve problems, and engage in metacognition. According to the teachers, HOTS-based reading literacy assessment aims to enable students to think critically, solve problems, and think creatively and innovatively. HOTS questions are formulated by providing texts to students and asking questions that require students to identify implied meanings in the text, draw conclusions based on the provided text, or analyze using various sources. The main challenges faced by teachers in implementing HOTS-based literacy assessment are students' limited vocabulary, students’lack of interest in reading, students’ lack of creative thinking, limited students' abilities, and insufficient time available for learning English.